Was Ugo Foscolo (1778–1827) affected by alpha-1 antitrypsin deficiency?. (February 2018) - Perciaccante, A.; Negri, C.; Coralli, A.; Charlier, P.; Appenzeller, O.; Bianucci, R.
Abstract: Niccolò Ugo Foscolo (1778–1827), known as Ugo, is one of the masters of the Italian poetry. A writer and a revolutionary, he embraced the ideals of the French Revolution and took part in the stormy political discussions, which the fall of the Republic of Venice had provoked. Despite his poor health, Foscolo lived an adventurous life serving as a volunteer in the Guardia Nazionale and in the Napoleonic army. Following Napoleon's fall (1814), he went into voluntary exile in early 1815. He reached London in Sept. 1816 and lived in poverty at Turnham Green (Chiswick) until his premature death. Foscolo's medical history has been poorly investigated and the cause of his death remains unclear. In an attempt to shed light on his clinical history, we analyzed his Correspondence ( Epistolario ), a series of more than 3000 letters written between 1794 and 1827. From the age of 26 (1808), Foscolo had frequent episodes of cough and dyspnea that progressively worsened. Four acute respiratory exacerbations occurred in 1812. Between September 1812 and April 1813, he had breathlessness as that of asthma. Frail and ailing, he developed a chronic liver disease in 1826. In August 1827, weakness, dyspepsia and drowsiness further increased and dropsy became manifest. He went into coma on September 7, 1827 and died aged 49 three days later. Based on a brief history of urethritis and urinary obstructions (1811–1812), previous scholars have suggested that Foscolo had urethral stenosis that caused a chronic bladder outlet obstruction and led to consequent renal failure. This hypothesis, however, does not mention the respiratory symptomatology present since 1804, which is a pivotal feature of Foscolo's illness. We surmise that Foscolo suffered from alpha-1 anti trypsin (AAT) deficiency, a rare genetic disease, which caused his premature death and support our interpretation with documental evidence.